2010
DOI: 10.1002/bem.20620
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent interaction of ultrashort E-fields with nociceptor membranes and proteins

Abstract: We examined the influence of ultrashort pulses (USP) on sensory neurons. Single and high frequency bursts of 12 ns E-fields were presented to rat skin nociceptors that expressed distinct combinations of voltage-sensitive proteins. A single E-field pulse produced action potentials in all nociceptor subtypes at a critical threshold (E(c) ) of 403 V/cm. When configured into high frequency bursts, USP charge integrated to reduce the action potential threshold in a frequency and burst duration-dependent manner with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…4,5 Jiang and Cooper demonstrated that a single, 12 ns nsPEF at 403 V∕cm was capable of activating skin nociceptors. 14 They were able to demonstrate this same effect at 100 pulses delivered at 4000 Hz with very low voltages (16.7 V∕cm).…”
Section: Introductionmentioning
confidence: 77%
“…4,5 Jiang and Cooper demonstrated that a single, 12 ns nsPEF at 403 V∕cm was capable of activating skin nociceptors. 14 They were able to demonstrate this same effect at 100 pulses delivered at 4000 Hz with very low voltages (16.7 V∕cm).…”
Section: Introductionmentioning
confidence: 77%
“…With this strategy, measurement of membrane currents was possible as soon as 5 s after NEP exposure. Jiang and Cooper (2012) used an entirely different strategy in their studies of NEP effects on sensory neurons. During exposure of patched neurons to high-intensity NEP(s), the patch clamp pre-amplifier was physically disconnected from the amplifier during the time of pulse delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that a single high-amplitude stimulus of 350- 100-, 12-, 5-, 4-, and even 1-ns duration can activate nerve, muscle, and endocrine cells [1318]. The thresholds varied for the different targets, but overall they expectedly became higher for shorter stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-rate nsEP trains could elicit action potentials even at low amplitudes. For example, delivering 12-ns pulses in 25 ms, 4 kHz bursts reduced the threshold for isolated nociceptor neurons from 0.4 to 0.016 kV/cm [13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation